Quantitative trend analysis of luxury fashion based on visual impressions of young Japanese women. Issue 2 (4th May 2017) - Furukawa, Takao; Miura, Chikako; Miyatake, Keiko; Watanabe, Asuka; Hasegawa, Makoto
ABSTRACT: This study aims to quantify chronological changes in the fashion trends of luxury brands by evaluating young Japanese women's impressions of ready-to-wear product photographs. As an objective and quantitative method, we conducted a cluster analysis on pairs of adjectives to determine a set of 14 semantic differential (SD) scales. These scales were then used to measure the impressions of the images. The SD analysis was applied to 128 sets of images, comprising designs from four luxury brands for two seasons in each year from 2000 to 2015. Chronological changes in SD scores reveal the dynamics of luxury fashion brands during the 16 years since 2000. Furthermore, the factor analysis of the SD data reveals four main influencing factors: colour, orthodoxy, decorative, and girlish. The results show significant differences among these luxury brands as measured by the visual impressions of female ready-to-wear products that correspond to their fundamental design identity from past to future.